Morphometric variations of three species of harvested cephalopods found in northern sea of Aceh Province, Indonesia (Biodiversitas Journal of Biological Diversity, 2014)
Muchlisin ZA, Zulkarnaini B, Purnawan S, Muhadjier A, Fadli N, Cheng SH. 2014. Morphometric variations of three species of harvested cephalopods found in northern sea of Aceh Province, Indonesia. Biodiversitas 15: 142-146. The purpose of the present studywas to evaluate the morphometrics of three harvested cephalopods, Sepioteuthis lessoniana, Sepia officinalis and Uroteuthis sp. found innorthern sea of Aceh Province, Indonesia. Sampling was conducted for six months from July to December 2012 in one week interval. Atotal of 318 cephalopods; 139 Sepioteuthis lessoniana, 139 Uroteuthis sp. and 40 Sepia officinalis were analyzed for morphometricstudy and 13 anatomical characters were measured to the nearest 0.01 mm using a digital caliper. Morphometric measurements weresignificantly different between the different species of cephalopods (ANOVA, p
Keywords: Morphology, Malacca strait, Sepioteuthis lessoniana, Sepia officinalis, Uroteuthis